EXISTENCE OF CUSTOMARY INSTITUTIONS KEUJRUEN BLANG IN IMPROVING RICE PRODUCTION MANGGENG ACEH SOUTHWEST - Furqan, M Hafizul (Universitas Pendidikan Indonesia, 2018)
The aim of this research is to analyze the influence of the existence of Keujruen blang customary institution to increase the yield of rice farmer of Manggeng Southwest Aceh. The study was conducted in 2016 against 54 farmers and 17 respondents Keujruen blang. Data collection using questionnaires, interviews and in-depth observation. Data processing using Likert scale and percentage of respondents answers to know the existence of Keujruen blang customary institution in improving the yield of Manggeng farmers. The result of the research shows that most (85,5%) of the respondents positive answer to the existence of Keujruen blang customary institution can increase the production of paddy farming of Manggeng farmers in order to improve the farming prosperity and food security in the future